Using Google Classroom as Media for Learning English during Pandemic - Fahriany Fahriany; Qurrotu Aini; Nida Husna; Didin Nuruddin Hidayat; Waliyadin Waliyadin; Agus Sufyan (Pioneer: Journal of Language and Literature, 2022)
Google Classroom is one of the platforms that can be utilized to help learn and is one of the platforms that can be used to assist in e-learning. This study aims to investigate the students’ views regarding the use of Google Classroom as a medium for English learning. This study employed a quantitative descriptive method in the form of an online survey by recruiting 90 students from five classes to voluntarily fill in an online survey using Google Forms. With the highest mean score of 4.06, the students admitted that Google Classroom makes it easy to sign, send, and receive the assignment. This finding indicated that students were satisfied with the aspects of Google Classroom, including accessibility, perceived utility, communication and interaction, and satisfaction with the learning activities offered by Google Classroom.